"The art of visible speech": infernal and purgatorial figurations in Great Expectations and A Tale of Two Cities - Fanucchi, Sonia (My University, 2010)
Abstract This dissertation is a study of the Dickensian imagination, focussing on the power of Dickens’s symbolism in Great Expectations and A Tale of Two Cities. Although Dickens believed himself to be a realist, this thesis explores a particular way in which his narrative style departs from realism as it came to be formulated by George Eliot and Gustave Flaubert. I argue that Dickens’s symbolism, intuitive and even chaotic as it seems, is informed by his exposure to works of allegory through reading and performance. Thus he evokes allegorical patterns of Dante, Bunyan and the Medieval Morality tradition to infuse his depiction of reality with a transcendent life. This gives it a greater dramatic intensity which effects a turn towards allegory. In a critical, evaluative study of the two novels, the dissertation foregrounds the relationship between the real and the allegorical strands of Dickens’s narrative. This is an artistic question but it is bound up with an ideological enquiry into the connection that Dickens makes between the secular and the religious. The balance between these two poles of Dickens’s vision differs in each novel but it is at its most effective in Great Expectations where the allegorical dimension arises seamlessly out of the material.